A Digital-Based Tourism Promotion Strategy to Increase Tourist Visiting to Archaeological Sites at Leleka Village, Wolasi District, South Konawe Regency - Hermina, Sitti; Alim, Abdul; Salniwati, Salniwati; Hadi, Arie Toursino; Aspin, La Ode (Journal of Community Service and Society Empowerment, 2026)
A digital-based tourism promotion strategy is a way to increase tourist visiting to Archaeological Sites at Leleka Village, Wolasi District, South Konawe Regency. This service community has objective to develop knowledge about enhancing digital-based tourism promotion of Archaeological remains. This community service activity uses an educational method. The primary target group is the community in Leleka Village, Wolasi District, South Konawe Regency, who are directly or indirectly involved in the management and development of the archaeological site for tourism destination, namely Kumapo Cave. The result indicates that this digital-based promotion strategy affects many tourists visiting by reason of there are many Archaeological cave sites with historical values and significant potential cultural tourism. The implication of this community service gives to the local society to care and protect their tangible cultural heritage and promote to the social media or in digital platform.